Analysis of natural sampled PWM switching strategy for a cascaded multilevel inverter using double integral fourier method - Razali, Azziddin Mohamad (Institute of Electrical and Electronics Engineers, 2005)
This paper describes a method to obtain a closed-form solution of the PWM output voltage waveform using a technique known as the double integral Fourier series expansion. A thorough treatment of on the mathematical derivation spectra of output voltage of a cascaded five-level inverter using this approach is given. This is followed by a verification of the results using practical results from a specially built test-rig. In addition, the harmonic spectra obtained from the closed-loop solution are compared with the calculation using the MATLAB time-based simulation.